Gut Microbiota Profile in Endometriosis Patients at Dr. M. Djamil Padang, West Sumatra, Indonesia - Haviz Yuad; Utama, Bobby Indra; Lipoeto, Nur Indrawaty; Putra, Andani Eka (Andalas Obstetrics And Gynecology Journal, 2025)
Objective: Endometriosis (EMS) is a chronic gynecological condition affecting up to 10% of women worldwide. The pathogenesis associated with hormonal imbalance, immune dysregulation, and changes in the gut microbiota. Gut microbiota dysbiosis may drive chronic inflammation that contributes to the progression of EMS. This study hypothesizes that certain gut microbiota profiles are associated with these factors in EMS patients, potentially developing non-invasive diagnostics and more targeted therapies. Methods: This is an observational analytical study with a case-control design conducted at Dr. M. Djamil Padang General Hospital in May 2024 with a sample size of 44 people. Case samples were women aged 18–40 years who were diagnosed with endometriosis based on the inclusion criteria, while the control group were women of reproductive age without a diagnosis of endometriosis. Data testing used the Next Generation Sequencing method, microbiome analysis test, and SPSS test. Results: The majority of EMS patients were aged 30-37 years, married, and had Nullipara obstetric status. In addition, the gut microbiota was dominated by the phyla Bacteroidetes and Firmicutes. Conclusion: There is a relationship between gut microbiota dysbiosis and the incidence of endometriosis, namely an increase in Bacteroidetes and a decrease in Firmicutes Keywords: endometriosis, dysbiosis, bacteroides, firmicutes, gut microbiota